1154 Skeletal muscle chloride channel gene (CLCN1) copy number variation can cause myotonia congenita. Issue 3 (9th February 2012) - Rayan, D Raja; Haworth, A; Sud, R; Matthews, E; Fialho, D; Burge, J; Portaro, S; Toscano, A; Davis, M D; Hanna, M G
Abstract : Myotonia Congenita (MC) is the commonest skeletal muscle channelopathy. It associates with recessive or dominant mutations in the chloride channel gene CLCN1. A significant number of patients from recessive pedigrees (14% in our series of 439 cases) only harbour a single recessive mutation despite full sequencing of CLCN1. The genetic basis of such cases remains unexplained; introducing uncertainties for diagnosis and genetic counselling. We hypothesised that CLCN1 copy number variations (CNV) may be a new genetic mechanism in such MC patients. We performed detailed clinical and neurophysiological characterisation in 60 patients with a MC phenotype. DNA sequencing of CLCN1 was followed by multiplex ligation dependent probe amplification (MLPA) to screen for CNV in CLCN1. We identified the first reported group of MC patients with CNV in CLCN1. Eight per cent of cases in our cohort carried a CNV in CLCN1. In two families, rearrangements affecting exons 8 to 14 had a very severe infantile onset myotonia. This indicates that CLCN1 CNV are an important previously unreported cause of recessive MC suggesting that MLPA should be done in the genetic work-up of patients with MC; especially in cases where direct DNA sequencing identifies no mutations or only a single recessive mutation. These data also indicate that additional unidentified genetic mechanisms exist to account for cases not currently explained by either exonic CLCN1 point mutations or copy number variation.